Konceptualizacja doświadczenia prawnego a konceptualizacja faktów związanych z funkcjonowaniem administracji : między nauką prawa administracyjnego a nauką administracji z badań wrocławskich i włoskich administratywistów - Nowak, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Conceptualization of legal experience and conceptualization of facts related in the functioning of the administration of the science of administrative law and administrative science in research of studies from school of Wrocław and Italian scholars administrative. The aim of this article is to describe the conceptions of legal experience and administrative legal facts, but on the other hand also to accentuate and underline influence on the administrative law and administrative science. The article is based on the research of professors F. Longchamps de Bérier, A. Błaś, J. Jeżewski, J. Korczak, but also Italian writers. The first part of the article is dedicated to description of a role of legal experience in administrative research. The last part of the paper present research of Professor A. Błaś and his concept of administrative legal facts, also of the light connection between theory and practice in administrative law. The results of the investigation remind (on the base of scientific achievements of Prof. A. Błaś) that the “reality” can be a part of implementation of the norms of administrative law, also of the light didactic issues
Keywords: administracja; prawo administracyjne; teoria; Polska; Włochy